Analisis Penerapan Kurikulum Merdeka Dalam Pembelajaran Pendidikan Agama Islam Di Madrasah Ibtidaiyah - Munawir, Munawir; Lailun Nurul Arofah; Sari, Roukhillah Anggraini Puspita (Universitas Islam Ahmad dahlan, 2024)
The Indonesian government introduced a new curriculum system in all educational institutions through the implementation of an independent curriculum. The purpose of this literature review is to find out, understand and evaluate the application and ideas related to subject matter, especially those concerning the implementation and creation of an independent curriculum in Islamic Religious Education subjects at MI. Therefore, the curriculum is very important for education and has a strong legal basis thanks to state law. Differentiated learning, namely teaching methods created to meet each student's unique learning needs, is a key component of the benefits of an independent curriculum. With its potential, the Independent Islamic Religious Education Curriculum aims to equip students with a more comprehensive and focused education. It is hoped that with proper development, this curriculum will produce students who meet the profile of Pancasila students, namely people who have faith, knowledge and noble character.